PENDIDIKAN LITERASI KEUANGAN DALAM PROGRAM MENABUNG PADA KELOMPOK B DI RA AL-JIHAD KOTA MALA - Anggraini, Dewi (Jurnal Penelitian Anak Usia Dini, 2023)
The purpose of this study was to determine the implementation of financial literacy education in the savings program and to determine the results of financial literacy education in the savings program This research method uses a qualitative approach with a case study type of research. This research uses qualitative data in the form of descriptive, data sources obtained through interviews, observation, and documentation. Data collection techniques used in data collection using structured and semi-structured interviews. The data analysis process uses data preparation, understanding data, knowing data, and combining data. Data validity was carried out using source triangulation and technique triangulation methods. The results of this study indicate that, in the application of financial literacy education in the saving program at RA al-Jihad Malang City, has 3 processes. the first process, there is an unwritten plan made by the school because the basis of this program is a habituation program, the second process, in this school implementing this program is carried out every day and voluntarily, the results of this study make children learn about finance The results of this study make children understand about finance in general, starting from the nominal money, how to manage money, and how to value money